High HDL-Cholesterol Levels Are Associated With Lower Risk of Acute Coronary Syndromes in Coronary Artery Disease - Aurélien Clerc; Serban Puricel; Yannick Faucherre; Jean-Luc Magnin; Sonja Lehmann; Dorian Garin; Charlie Ferry; Pascal Meier; Mario Togni; Stephane Cook (Journal of Interventional Cardiology)
Trial Registration: ClinicalTrials.gov identifier: NCT04185285